Surgery-induced reactive oxygen species enhance colon carcinoma cell binding by disrupting the liver endothelial cell lining. Issue 8 (27th January 2011) - Gül, Nuray; Bögels, Marijn; Grewal, Simran; van der Meer, Anne Jan; Rojas, Lucy Baldeon; Fluitsma, Donna M; van den Tol, M Petrousjka; Hoeben, Kees A; van Marle, Jan; de Vries, Helga E; Beelen, Robert H J; van Egmond, Marjolein
Abstract : Objective: Resection of primary colorectal cancer is associated with enhanced risk of development of liver metastases. It was previously demonstrated that surgery initiated an early inflammatory response resulting in elevated tumour cell adhesion in the liver. Because reactive oxygen species (ROS) are shown to be produced and released during surgery, the effects of ROS on the liver vascular lining and tumour cell adhesion were investigated. Methods: Human endothelial cell monolayers (human umbilical vein endothelial cells (HUVECs) and human microvascular endothelial cells of the lung (HMEC-1s)) were exposed to ROS production, after which electrical impedance, cellular integrity and tumour cell adhesion were investigated. Furthermore, surgery-induced tumour cell adhesion as well as the role of ROS and liver macrophages (Kupffer cells) in this process were studied in vivo. Results: Production of ROS decreased cellular impedance of endothelial monolayers dramatically. Moreover, formation of intercellular gaps in endothelial monolayers was observed, exposing subendothelial extracellular matrix (ECM) on which colon carcinoma cells adhered via integrin molecules. Endothelial damage was, however, prevented in the presence of ROS-scavenging enzymes. Additionally, surgery induced downregulation of both rat and human liver tight junction molecules. Treatment of rats with the ROS scavenger edaravone prevented surgery-induced tumour cell adhesion and downregulation of tight junction proteins in the liver. Interestingly, depletion of Kupffer cells prior to surgery significantly reduced the numbers of adhered tumour cells and prevented disruption of expression of tight junction proteins. Conclusions: In this study it is shown that surgery-induced ROS production by macrophages damages the vascular lining by downregulating tight junction proteins. This leads to exposure of ECM, to which circulating tumour cells bind. In light of this, perioperative therapeutic intervention, preventing surgery-induced inflammatory reactions, may reduce the risk of developing liver metastases, thereby improving the clinical outcome of patients with colorectal cancer.